Implementation of Independent Curriculum Learning at Cimone State Elementary School Tangerang City - Mia Alfiatun Najah; Yeni Nuraeni; Ina Magdalena (Jurnal PAJAR (Pendidikan dan Pengajaran))
This study aims to describe the implementation of the Independent Curriculum at SDN Cimone 1, this study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation studies. The school's efforts in facing various challenges and the readiness of teachers and principals in their implementation. The Merdeka Curriculum emphasizes flexibility, independence, and character development, so that the learning process becomes more relevant, adaptive, and fun for students. The results of the study show that the implementation of this curriculum involves the active role of teachers, the availability of resources, and the learning needs of students who are very diverse. Teachers are required to be more creative and adaptive in managing project-based learning, while students respond positively because they feel more free to express their interests and talents. The obstacles faced include limited facilities, uneven teacher readiness, and student adaptation to new and innovative learning methods. Strengthening teacher training, procurement of facilities, and increasing collaboration between schools and related parties is very necessary so that the implementation of the curriculum can run optimally and have a significant positive impact on the learning process in elementary schools as a whole.